2022
DOI: 10.1016/j.phyplu.2022.100241
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and structural insights of β-boswellic acid and glycyrrhizic acid as potent SARS-CoV-2 Envelope protein inhibitors

Abstract: Background : Over million people have been infected with SARS-CoV-2 virus worldwide, with around 3% reported deaths till date. A few conventional antiviral treatments have been tried to mitigate the coronavirus. However, many alternative therapeutics are being evaluated worldwide. In the present study, we investigated traditional Indian medicinal compounds antiviral potencies as an effective drug for targeting SARS-CoV-2E. SARS-CoV-2 E protein plays a key role in coronavirus life cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Recently, the activity of BAs, GR and several natural compounds was determined by studying molecular docking to measure the binding of these compounds to the SARS-CoV-2 E protein. BAs and GR were found to have strong antiviral activities against enveloped viruses because they are inhibitors of the SARS-CoV-2 E protein (Fatima et al 2022 ). Data from other bioinformatics studies suggested that BAs possess antiviral properties because BAs target SARS-CoV-2 viruses at an atomic scale on three functional proteins, which are responsible for human cell adhesion (spikes of the virus) or viral RNA replication (main proteins of SARS-CoV-2, Mpro) (Caliebe et al 2021 ; Kadhim et al 2021 ; Roy and Menon 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the activity of BAs, GR and several natural compounds was determined by studying molecular docking to measure the binding of these compounds to the SARS-CoV-2 E protein. BAs and GR were found to have strong antiviral activities against enveloped viruses because they are inhibitors of the SARS-CoV-2 E protein (Fatima et al 2022 ). Data from other bioinformatics studies suggested that BAs possess antiviral properties because BAs target SARS-CoV-2 viruses at an atomic scale on three functional proteins, which are responsible for human cell adhesion (spikes of the virus) or viral RNA replication (main proteins of SARS-CoV-2, Mpro) (Caliebe et al 2021 ; Kadhim et al 2021 ; Roy and Menon 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Acetyl 11-keto-β-boswellic acid has been recognized as a potential natural product for the treatment of various viral illnesses 26 , 92 . Boswellia plays a crucial role in various diseases, for instance, its serrata gum resin is already reported in inflammation, chikungunya, and vesicular stomatitis and β-boswellic acids are also reported against HSV-1, HIV, and herpes virus 93 96 . In the recent COVID-19 pandemic, boswellic acids with glycyrrhizin (GR) combination displayed successful actions against COVID-19 97 , 98 .…”
Section: Discussionmentioning
confidence: 99%
“…Fatima et al [70] The results show that glycyrrhizic acid interacts with E protein at Arg61, Phe23, Tyr57 and Val25, and so does β-boswellic acid with E protein at Leu34, Leu37, Arg38 and Leu39, thus resulting in the structural destruction of E protein. Glycyrrhizic acid and β-boswellic acid show their strong affinity with E protein in the screened compounds.…”
Section: Pharmacology Of Sars-cov-2 E Proteinmentioning
confidence: 98%